Perceived Impact Of Entrepreneurship On The Performance Of Small And Medium Enterprises (SMEs) In Nigeria. - Jerome, Nyameh; Timothy, Victor; Timothy, Victor (Advances in Social Sciences Research Journal, 2019)
The study examines the impact of entrepreneurship on the performance of SMEs in Nigeria to achieve the aim of the study the following research objectives and hypotheses were formulated these include; (i)To determine the impact of entrepreneurship on the performance of SMEs in Nigeria. (ii)To evaluate the nonperformance of SMEs in Nigeria (iii)To Examine the extent to which Entrepreneurship influence performance of SMEs in Nigeria and H0: there is no positive and significant relationship between entrepreneurship and performance of SMEs Hi: there is a positive and significant relationship between entrepreneurship and performance of SMEs. the research method adopted for the study was quantitative approach through survey questionnaire with five point Likert scale structure with twelve items questions distributed to 15 respondents who filled all the questionnaires and return 100%. The responses and analysis revealed that there is positive and significant relationship between entrepreneurship and performance of SMEs in Nigeria